Cover Image. (21st May 2022) - Sun, Hui; Li, Zhiyuan; Fan, Chun; Liu, Shuang; Yan, Kaixian; Huang, Guoqian; Li, Shu
Abstract : The cover image is based on the Research Article Slit guidance ligand 2 promotes the inflammatory response of periodontitis through activation of the NF‐κB signaling pathway by Shu Li et al., https://doi.org/10.1111/jre.12987 .